2020
DOI: 10.1111/jphs.12334
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ perspectives on care coordination for adults with cancer and multiple chronic conditions: a systematic review

Abstract: Objectives Inherent treatment complexities for patients with both cancer and multiple chronic conditions (MCC) make these patients likely candidates for shared care between primary care providers (PCPs) and oncologists. However, providers' views on the optimal model for care coordination between PCPs and oncologists in the context of both cancer and MCC are unclear. Thus, the purpose of this systematic review is to evaluate the perceptions of PCPs and oncologists regarding barriers and facilitators to care coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…This study confirms a number of previously identified concerns, including communication disparities resulting in an absence of role clarity between cancer specialists and GPs (Dossett et al, 2017;Easley et al, 2017;Lisy et al, 2020;Mitchell et al, 2012;Tsui et al, 2019), and a need for greater role clarity for PNs working in primary care (Aggar et al, 2016;Hohmann et al, 2020;McInnes et al, 2015McInnes et al, , 2017Yuille et al, 2016). Further, as previous studies highlighted,…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study confirms a number of previously identified concerns, including communication disparities resulting in an absence of role clarity between cancer specialists and GPs (Dossett et al, 2017;Easley et al, 2017;Lisy et al, 2020;Mitchell et al, 2012;Tsui et al, 2019), and a need for greater role clarity for PNs working in primary care (Aggar et al, 2016;Hohmann et al, 2020;McInnes et al, 2015McInnes et al, , 2017Yuille et al, 2016). Further, as previous studies highlighted,…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the complex health profiles of adult cancer survivors often include chronic medical conditions beyond cancer (Hohmann et al, 2020;Leach et al, 2015) and cancer survivors are less likely to receive optimal, holistic care if they do not see a primary care provider (Snyder et al, 2015). It is therefore critical that the involvement of primary care providers is optimised (Rubin et al, 2015;Vardy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in cancer screening and treatment have led to significant increases in the number of cancer survivors, each having a unique set of survivorship needs [ 1 , 2 , 3 , 4 , 5 ]. In Canada, survival for all cancers combined rose from 55% in the period 1992–1994 to 63% in the period 2012–2014 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCP and patient perspectives have been investigated with regard to transitioning from oncologist-led care to primary care [ 2 , 13 , 14 , 20 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Patients generally have confidence in PCPs to provide survivorship care, and support the use of a survivorship care plan (SCP) summarizing a patient’s cancer, cancer treatments, and recommended follow-up to facilitate this care [ 2 , 20 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation